TIME-RESOLVED RAMAN MEASUREMENT OF INTERVALLEY SCATTERING IN GASB - Maly, P; Maciel, A; Ryan, J; Mason, N; Walker, P (1994)
Time-resolved Raman spectroscopy with subpicosecond resolution has been used to measure L- Gamma intervalley scattering of photoexcited electrons in GaSb. Our experiment measures directly the time-dependent occupancy of non-equilibrium longitudinal optic phonons with wavevector approximately 10 6 cm -1 which are generated by intra- Gamma relaxation of electrons near the Gamma minimum. The phonon population shows a two-component decay: at times